Effect of in-office bleaching agents on the color changes of stained ceromers and direct composite resins. (November 2014) - Xing, Wenzhong; Jiang, Tao; Liang, Shanshan; Sa, Yue; Wang, Zhejun; Chen, Xiaodong; Wang, Yining
Abstract Purpose. To evaluate the effect of two in-office bleaching agents on the color changes of two ceromers (Ceramage and Adoro SR) and one direct composite resin (Gradia Direct Anterior) after staining by tea and coffee. Materials and methods. Twenty-four disk-shaped specimens were fabricated for each resin material and randomly divided into three groups (n = 8). The specimens were immersed in tea, coffee or deionized water, respectively, for 7 days. Each group was then equally divided into two sub-groups (n = 4), which were subjected to two in-office bleaching agents (BEYOND and Opalescence Boost), respectively. The color of the specimens was measured by a spectrophotometer at baseline, after staining and after bleaching. The color differences (ΔE values) between baseline and after treatments were calculated. Results. Statistical analysis indicated that the staining solution had significant influence on the color change of resin composites tested (p < 0.001). The discolorations of resin composites were perceptible after immersing in tea or coffee solutions (ΔE>2.0). There was no statistically significant difference between BEYOND and Opalescence Boost in stains removal from discolored resins (p = 0.550). The color changes in ΔE value between baseline and after bleaching were less than 2.0 for all resin composite groups. Conclusions. Tea solution produces severe discoloration of three resin composites tested. The two in-office bleaching agents can effectively remove the stains from two ceromers and one direct composite resin tested in this study.